2009
DOI: 10.1021/jp9021739
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Imaging and Tuning Subcellular Structures and Membrane Transport Kinetics of Single Live Cells at Nanosecond Regime

Abstract: We developed an electric-field exposure microchannel system with 230-nanometer thin-layer gold electrodes, and interfaced it with a single living cell imaging station and a 10-nanosecond-electric-pulse (10nsEP) generator. This design allows us to image intracellular molecules and structures, membrane transport and viability of single leukemic cells (HL60) while the cells are exposed to 10nsEPs of 0–179 kV/cm, permitting the study of subcellular responses at nanosecond regime. The electrodes confine a thin-laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…As already presented, the nanopulses should have little effect on the plasma membrane integrity. Numerous in vitro studies have confirmed this hypothesis on several cell lines: Jurkat lymphocyte cells [Ibey et al, 2010], HCT116 colon carcinoma cells [Hall et al, 2005], HL-60 leukemia cells [Xu et al, 2009], or B16F1 melanoma cells [Napotnik et al, 2010]. At higher electric fields or with an increased number of pulses, the cell and its organelles are irreversibly porated and undergo necrosis or apoptosis Ibey et al, 2010].…”
Section: In Vitro Studies Using Nanopulsesmentioning
confidence: 87%
See 2 more Smart Citations
“…As already presented, the nanopulses should have little effect on the plasma membrane integrity. Numerous in vitro studies have confirmed this hypothesis on several cell lines: Jurkat lymphocyte cells [Ibey et al, 2010], HCT116 colon carcinoma cells [Hall et al, 2005], HL-60 leukemia cells [Xu et al, 2009], or B16F1 melanoma cells [Napotnik et al, 2010]. At higher electric fields or with an increased number of pulses, the cell and its organelles are irreversibly porated and undergo necrosis or apoptosis Ibey et al, 2010].…”
Section: In Vitro Studies Using Nanopulsesmentioning
confidence: 87%
“…Because this protein is released from mitochondria it implies that the apoptosis induced by nsPEF is dependent on mitochondria, but it remains unclear if mitochondria are directly responding to the interaction with the electric field or if their involvement is a consequence of another primary event [Beebe et al, 2003a]. Different studies on leukemic cells (HL-60) have indicated that pulses as short as 10 ns also induce the condensation of intranuclear nucleic acids [Xu et al, 2009]. The effects of nsPEF have proven to be highly dependent on the electric field and pulse number but in a nonlinear fashion.…”
Section: In Vitro Studies Using Nanopulsesmentioning
confidence: 99%
See 1 more Smart Citation
“…The same number of the cells was used for control experiments. We exposed the cells to 25 sequential 10nsEPs of 150, 40 and 25 kV/cm (1-s pulse interval), provided by a 10-ns pulse generator (ARC Technology) as described previously [16]. The 10nsEPs were measured in real time using an oscilloscope (TDS 3052B, Tektronix) [16].…”
Section: Utilizing Pefs To Prepare Growth-arrested Feeder Cellsmentioning
confidence: 99%
“…Recent studies show that ultrashort electric pulses (e.g., 10 ns) can penetrate the cells and induce intracellular responses while maintaining viability of cells [16,17]. The intracellular structures and viability of cells depend on the number and electric-field strength (E) of the 10-ns electric pulses (10nsEPs), showing the possibility of tuning them to prepare a wide variety of viable growth-arrested cells.…”
Section: Introductionmentioning
confidence: 99%